Daily Enema Regimen Is Superior to Traditional Therapies for Nonneurogenic Pediatric Overactive Bladder. (4th March 2016) - Hodges, Steve J.; Colaco, Marc
Our objective was to evaluate the efficacy of daily enemas for the treatment of overactive bladder (OAB) in children. This study was a prospective, controlled trial of 60 children with nonneurogenic OAB. The control patients (40) were treated with standard therapies, including timed voiding, constipation treatment with osmotic laxatives, anticholinergics, and biofeedback physical therapy, whereas the treatment patients (20) received only daily enemas and osmotic laxatives. On assessment of improvement of OAB symptoms, only 30% of the traditionally treated patients' parents reported resolution of symptoms at 3 months, whereas 85% of enema patients did. At the onset of the study, the average pediatric voiding dysfunction score of all patients was 14, whereas on follow-up, the average scores for traditionally treated patients and enema-treated patients were 12 and 4, respectively. This study demonstrated that daily enema therapy is superior to traditional methods for the treatment of OAB.